Research on Air Pressure Cycle Test of Liquefied Petroleum Gas Cylinder. Issue 1 (March 2020) - Jia, Songqing; Han, Bing; Dai, Xingtao; Bo, Ke; Wei, Zhihao; You, Hongxin
Abstract: Air pressure cycle tests were performed on liquefied petroleum gas (LPG) high-density polyethylene liner glass fiber fully wound cylinders. During the repeated filling and discharging of the gas cylinder, the changes of the internal and external surface temperature and internal pressure of the gas cylinder with time were obtained. Through experimental analysis and numerical simulation, the characteristics of the flow field in the cylinder during the pressure cycle test at different pressure cycle rates were studied. The results show that the temperature in the gas cylinder rose steadily during the test. The temperature rise trend of the gas cylinder in Fluent simulation was the same as that in the test. In the air pressure cycle test, the temperature change of the cylinder was larger than that of the cylinder when it was filled with LPG, and the structure and material properties of the cylinder were unchanged. This test can check whether the LPG high-density polyethylene liner glass fiber fully wound cylinders are safe.